Evaluation of the ergonomic sitting position adopted by dental students while using dental simulators - Iriana Argentina Corrales Zúniga; Nahomy Lissette Sauceda Malespín; Alba Lucía Vega Vílchez; Octavio J. Duarte Frenky; Guang Hong; Juan Ramón Vanegas Sáenz (Elsevier, 2023)
Background/purpose: Ergonomics in dentistry encourages the work to be in an organized manner, where a dentist achieves highest performance with maximum comfort and minimum physical and psychological effort. The purpose of this study was to evaluate the ergonomic sitting position of dental students from third, fourth and fifth year undergraduate programs while they prepared teeth 46 and 27 as Black Class I preparation for amalgam using dental simulators. Materials and methods: Ten students were randomly selected from each year for this study. Photos and videos were taken from them to record their sitting position as they performed a Black Class I amalgam preparation in Nissin simulators. Results: It was found that more students had a poor ergonomic sitting position while working in mandibular area (60%, torso and neck angle; 53% knee-angle; 50% elbow-angle). When comparing the average score between maxilla and mandible within students of the same year, fourth year students had a significant difference in their average, with a better performance in maxilla (P ≤ 0.01). They also showed better performance in maxillary area compared to fifth-year students (P ≤ 0.008). The main reasons that the students presented as justification for their bad posture were little work time, lack of knowledge, not knowing how to use indirect vision, and poor comfort. Conclusion: Every undergraduate year had a compromised sitting position, with the exception of fourth-year students when working in maxillary area. No correlation between undergraduate year and performance was found.